Event Planning & Management System - Mohammad, Ratna Mutiara (IRC, 2020)
Event Planning & Management System is a mobile application that will be developed as an effort to help ease the work of newly assigned event coordinators, specifically in planning and managing corporate events such as town halls, corporate dinners, team buildings, corporate social responsibilities and engagement sessions. Since for most corporate events, their event coordinators will always keep on changing between the employees within the company, this makes it difficult for newly assigned coordinators to understand their work instructions without having to manually seek out the previous coordinators verbal explanations and guidance. This application is developed using Microsoft PowerApps Canvas Application because it is suitable to create custom applications and is able to leverage the multiple features that are available from Office 365 and Microsoft platform.